Hypertension and Migraine: A Bibliometric Analysis - Ramadan, Heba (Headache Medicine, 2024)
Introduction Hypertension, or high blood pressure, is a common and serious health issue. It has no specific symptoms, and for that, it is called the silent killer. Migraine attacks may be alarming for those with hypertension. Objective This review aims to analyze the trending publications concerning hypertension and migraine. Methods This bibliometric analysis analyzed the trending publications about hypertension and migraine. The Scopus database was used, and the bibliometric analysis was applied to show the most productive authors, the journals that most contributed in this field, countries, institutions, and keywords used. Hypertension and migraine showed elevated growth in the published articles throughout the years. Results For the last ten years, from 2013 to 2022, there has been a dramatic increase, especially in the last few years in publications related to hypertension and migraine. The highest number of publications were in the United States, the most productive authors being Dodick, D.W. and Pezzini, A., Harvard Medical School had the most published articles; and Headache journal was on the top 10 journals that had publications on this subject. Conclusion Migraine is recently considered a sign of hypertension, and this bibliometric analysis focused on the remarkable interest that has appeared in the research community.